Faktor-Faktor Hygiene dan Motivator: Pengaruhnya terhadap Kepuasan Kerja Perawat di Rumah Sakit Baptis Batu - Kolibu, Febi Kornela; Rachmi, Asih Tri (Universitas Brawijaya, Indonesia, 2014)
The aims of this study is to identify the factors that affect nurses'job satisfaction at Rumah Sakit Baptis Batu (RSBB). This analysis used analytical descriptive method with cross sectional approach. Respondents are all of the nurses who are working in RSBB, sixty seven persons in total. Multiple linear regression test showed that, simultaneously, hygiene and motivator factors have significant effect on the job satisfaction with a significance value of 0.000. Partially, motivator factors constitute influential variable that affecting the job satisfaction with a significant value of 0.001 and dominant variable of the job satisfaction with a beta value of 0.620.